Clinical and instrumental evaluation of a new topical non-corticosteroid antifungal/anti-inflammatory/antiseborrheic combination cream for the treatment of mild-to-moderate facial seborrheic dermatitis - Dall'Oglio F; Lacarrubba F; Luca M; Boscaglia S; Granger C; Micali G (Dove Medical Press, 2019)
Federica Dall’Oglio,1 Francesco Lacarrubba,1 Maria Luca,1 Simona Boscaglia,1 Corinne Granger,2 Giuseppe Micali1 1Dermatology Clinic, University of Catania, Catania, Italy; 2Innovation and Development, ISDIN SA, Barcelona, Spain Purpose: Topical agents play a key role in the management of facial seborrheic dermatitis (SD) by reducing inflammation and scale production. The aim of this open-label trial was to assess the efficacy and tolerability of a new non-corticosteroid, antifungal/anti-inflammatory/antiseborrheic cream containing piroctone olamine, stearyl glycyrrhetinate, and zinc PCA in the treatment of facial SD using clinical and instrumental evaluation. Patients and methods: Twenty adult subjects affected by mild-to-moderate inflamed facial SD were enrolled and instructed to apply the study cream twice daily for 60 days. Efficacy was evaluated at baseline, and at days 15, 30, and 60 by measuring the grade of desquamation, erythema, and pruritus using clinical evaluation, erythema-directed digital photography, colorimetry, and subject-completed Visual Analog Scale. Additionally, an Investigator Global Assessment (IGA) was assessed using a 5-point scale: excellent response (>80% improvement); good response (50%–80% improvement); mild response (<50% improvement); no response (no change); worsening. Results: After 15 days, a statistically significant decrease from baseline was found in desquamation, erythema, colorimetric scores, and pruritus. At day 60, a significant further improvement for all evaluated parameters was recorded. Moreover, the IGA improved in 90% of patients, with an excellent response in 53% of cases. A good correlation was found between clinical and instrumental evaluations. Conclusion: Our results indicate that the study facial cream represents an option to consider when dealing with mild-to-moderate SD, being effective, well-tolerated, and free of significant side effects, as confirmed by clinical and instrumental evaluation. Keywords: seborrheic dermatitis, topical cosmetic, digital photography, colorimeter